ENGLISH LANGUAGE TEACHING IN PRIMARY SCHOOLS IN MAKASSAR: TEACHERS’ PERCEPTIONS - Sirajuddin Kamal (Kajian Linguistik dan Sastra, 2007)
Teachers are one of the most important parts in the discourse of education andthe process of teaching and learning in schools. It was this that interested the writerto research their perceptions of English language teaching for primary students.The respondents are five participants from different primary schools in Makassar.They were asked to comment on their beliefs in terms of the materials used in theclassrooms, the aims of teaching English for primary students, their problems inrelation to professional knowledge, classroom practices and context (school andcommunity), and their way to resolve many problems. The responses are groupedinto four major categories in terms of the aims of the research and examined toexplore similarities and differences. The result showed that when the materials areabout familiar topics and are presented through songs, games, and pictures, in theclassroom they result in positive student attitude and increase interest and motivationin learning English. Participants feel that the main aim of teaching English foryoung students is to provide them with as much vocabulary as possible before theymove on to higher education. Finally, some constraints of the program are alsofound in the classroom practices.